Penyingkapan Diri Perempuan Penyintas Kekerasan Seksual - Rini Oktaviani; Suzy S. Azeharie (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2020)
The high rate of sexual violence including rape and sexual harassment in Indonesia is a problem that has not been resolved. However, it cannot be concluded that cases of rape and sexual harassment are increasing, but more and more women survivors report cases they have experienced. Women dare to speak and not be influenced by the opinion of the majority who blame victims of sexual violence. One interesting phenomenon to be reviewed is the self-disclosure of women survivors of rape and sexual harassment of consorts. This study aims to determine the self-disclosure by women survivors of rape and sexual harassment at the escort and the reasons for women survivors of rape and sexual harassment to disclose themselves to the companion. The theory used is the theory of interpersonal communication, self-disclosure, the spiral of silence and patriarchal culture. This study uses a descriptive qualitative approach with the phenomenological method. Data analyzed were obtained from interviews with four survivors of rape and survivors of sexual harassment. The results of this study are the disclosure of survivors of rape and survivors of sexual harassment to companions is important so that victims do not bear their own problems and can immediately recover. Survivors can find people who at least have experience in support and people who can be trusted to listen to self-disclosure. But different things were found in the companion who is the mother of survivors and sexual harassers. The survivor's mother ignored the incident of abuse experienced by the survivor and assumed that the incident had never happened because the perpetrator was a person who was of one flesh and blood with the survivor. Tingginya angka kekerasan seksual termasuk perkosaan dan pelecehan seksual di Indonesia menjadi permasalahan yang sampai saat ini belum terselesaikan. Namun tidak dapat disimpulkan bahwa kasus perkosaan dan pelecehan seksual semakin bertambah melainkan semakin banyak perempuan penyintas yang melaporkan kasus yang mereka alami. Perempuan berani bersuara dan tidak terpengaruh dengan pendapat mayoritas yang menyalahkan korban kekerasan seksual. Salah satu fenomena yang menarik untuk diulas adalah penyingkapan diri perempuan penyintas perkosaan dan pelecehan seksual pada pendamping. Penelitian ini bertujuan untuk mengetahui penyingkapan diri yang dilakukan perempuan penyintas perkosaan dan pelecehan seksual pada pendamping dan alasan perempuan penyintas perkosaan dan pelecehan seksual melakukan penyingkapan diri pada pendamping. Teori yang digunakan adalah teori komunikasi interpersonal, penyingkapan diri, spiral keheningan dan budaya patriarki. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode fenomenologi. Data yang dianalisis diperoleh dari hasil wawancara dengan empat penyintas perkosaan dan penyintas pelecehan seksual. Hasil dari penelitian ini adalah penyingkapan diri penyintas perkosaan dan penyintas pelecehan seksual pada pendamping penting dilakukan agar korban tidak menanggung masalahnya sendiri dan dapat segera memulihkan diri. Penyintas bisa mencari orang yang setidaknya mempunyai pengalaman dalam mendukung dan orang yang bisa dipercaya untuk mendengarkan penyingkapan diri. Namun hal berbeda ditemui pada pendamping yang merupakan ibu dari penyintas dan pelaku pelecehan seksual. Ibu si penyintas mengabaikan peristiwa pelecehan yang dialami penyintas dan menganggap bahwa peristiwa tersebut tidak pernah terjadi karena pelaku adalah orang yang satu darah daging dengan penyintas.